Strategi Guru PAI Mengatasi Kesulitan Belajar Peserta Didik di SMPN 1 Corawali Kabupaten Sidrap - Syalina, Wanda Sulfina; Ahmad, Ahmad; Wahab, Abdul (LP2M Universitas Islam Ahmad Dahlan, 2025)
A qualitative case study conducted at SMP Negeri 1 Corawali, Sidrap Regency, investigated learning difficulties experienced by eighth-grade students in Islamic Religious Education. These difficulties were identified in cognitive aspects (comprehension and retention of religious material), affective aspects (low motivation and learning interest), and psychomotor aspects (inadequate ability to read the Qur'an with proper tajwid). Data were collected through participant observation, semi-structured interviews, and document analysis. The results showed the implementation of an integrated learning strategy combining individual approaches, the formation of positive learning habits, and counseling guided by Islamic values. The success of this strategy was influenced by teacher dedication, the quality of the teacher-student relationship, and support from the school and family. However, the main challenges faced included the heterogeneity of students' academic abilities, limited learning resources, and minimal learning support from the home environment.